East Mediterranean gas: A new arena for international rivalry - Ahmed ElBassoussy (Review of Economics and Political Science (REPS), 2018)
Purpose - This paper aims to explore the international response to the discovery and development of gas fields in the East Mediterranean basin. Design/methodology/approach - The study applies key concepts into a framework and explores the strategies used by nations for developing their influence in the region. Findings - The key nation states (the USA and Russia) and the supranational EU are notable in their divergent approaches to obtaining access to and influence regarding the gas fields. Practical implications - The development of the strategies used by the international rivals for access to the resources available from the offshore oil fields is set to be an area for further study. Originality/value - This paper offers insight into a developing rivalry over energy security, which will a platform for further investigation throughout the exploitation of the "New Gulf" gas fields.
Keywords: 330; Pipeline; Energy security; Gas facilities; Concession area; Energy dependency; Offshore field; Liquefied natural gas; Exclusive economic zone; Estimated reserves; Hydrocarbons; East Mediterranean